Tecnologias da informação e comunicação: um estudo qualitativo com docentes do Curso de Pedagogia - Oliveira, Valéria Alves de (2015)
The information and communication technology (ICT) is present in several areas, causing many changes in social and private spaces. Before that, quality education is being increasingly challenging, since the teacher must be aware of the characteristics of today's world, new needs and expectations in order to contribute significantly to the realization of this fundamental role of higher education to prepare critical teaching and active citizens in the society. Information and Communication Technologies as a teaching resources provides new ways of teaching and learning. However, both the teacher future professional of education need to master, and appropriate these resources in order to innovate their pedagogical practice, as ICTs demand more than the technical skill. The objective of the study was to analyze how teachers of the pedagogy course in a private university in the state of Rio Grande do Sul used ICTs in their pedagogical practices for the preparation of future teachers. This study is justified by the need to further explore the issues related to the use of ICTs by teachers who work in the course of pedagogy in the preparation of future teachers. The research was qualitative interpretative nature. The technique for data collection was semi-structured individual interviews. The selection of the sample of respondents followed the snow-ball strategy and the final sample consisted of thirteen teachers (a total of twenty-two teachers). The main results of the study were: the valuation of scientific knowledge in both the action of the higher education teacher and the practice of the future professional of education, ability to technically operate the technological resources as the main knowledge to teach the use of ICTs to only convey information in order to continue to focus on the same traditional teaching practices and the recognition of the importance of using technologies in teaching education and the need for continuing education to provide teachers innovative pedagogical experiences.